Spatiotemporal fractionation schemes for irradiating large cerebral arteriovenous malformations - Unkelbach, Jan (Int J Radiat Oncol Biol Phys, 2016)
PURPOSE AND OBJECTIVES: We consider fractionation effects in the context of radiosurgery treatments of large cerebral arteriovenous malformations (AVM). In current practice, fractionated treatments divide the dose evenly into several fractions, which generally leads to low obliteration rates. In this work, we investigate the potential benefit of delivering distinct dose distributions in different fractions. METHODS AND MATERIALS: Five patients with large cerebral AVMs were reviewed and were replanned for intensity-modulated arc therapy delivered with conventional photon beams. Treatment plans allowing for different dose distributions in all fractions were obtained by performing treatment plan optimization based on the cumulative biologically effective dose (BED) delivered at the end of treatment. RESULTS: We show that distinct treatment plans can be designed for different fractions such that high single fraction doses are delivered to complementary parts of the AVM. All plans create a similar dose bath in the surrounding normal brain and thereby exploit the fractionation effect. This partial hypofractionation in the AVM along with fractionation in normal brain achieves a net improvement of the therapeutic ratio. We show that a biological dose reduction of approximately 10% in the healthy brain can be achieved compared to reference treatment schedules that deliver the same dose distribution in all fractions. CONCLUSIONS: Boosting complementary parts of the target volume in different fractions may provide a therapeutic advantage in fractionated radiosurgery treatments of large cerebral AVMs. The strategy allows for a mean dose reduction in normal brain that may be valuable for a patient population with an otherwise normal life expectancy.